Three Epigraphs from the “Rigveda” (Siamanto, Daniel Varuzhan, Yeghishe Charents) - Grigoryan, Seyran (Bulletin of Yerevan University B: Philology, 2022)
The article is dedicated to three epigraphs, which were taken by Armenian poets from the “Rigveda” at the beginning of the 20th century. In 1902, Siamanto (Atom Yardzhanyan) published the first collection of poems, the epigraph of which was the line “There are many dawns that have not yet lit up” with an indication of the source “Rigveda”. In 1908, another Western Armenian poet, Daniel Varuzhan, wrote the poem “Light”, the epigraph of which was also taken from the ancient Indian hymnbook (“You shine for greatness and sacrifice”). The epigraph of Siamanto in the “Rigveda” is dedicated to the god of justice Varuna, and the epigraph of Varuzhan is dedicated to the fire god Agni. In 1918, Yeghishe Charents’ poem “Soma” was published, which was dedicated to the god of the sacred drink of the Hindus. The epigraph of the poem was another line of the “Rigveda” – “Soma, you are the last freedom”. The article explains the exact or hypothetical sources of three epigraphs in the text of the “Rigveda”. In the article there are considered ideological and aesthetic content of the epigraphs, the role that these epigraphs play in the poetics of the works of three Armenian poets and artistic connections with ancient Indian mythology and poetry. The author concludes that the use of Vedic hymns testifies the effective influence of the “Rigveda” on Armenian literature.